2007
DOI: 10.1007/s11127-007-9253-y
|View full text |Cite
|
Sign up to set email alerts
|

Political freedom, economic freedom, and income convergence: Do stages of economic development matter?

Abstract: Income convergence, Economic freedom, Political freedom, Stages of development, OECD countries, C12, C23, O53, O57,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…3. See Easton and Walker (1997), Ayal and Karras (1998), Dawson (1998Dawson ( , 2003, De Haan and Sierman (1998), Gwartney, Lawson, and Holcombe (1999), Wu and Davis (1999), De Haan and Sturm (2000), Carlsson and Lundstrom (2002), Justesen (2008), Xu and Li (2008), Faria andMontesinos (2009), andGwartney (2009). relationship between the level of economic freedom and income inequality, Scully (2002) finds that higher levels of economic freedom are associated with lower levels of income inequality. Both studies use the Fraser Institute Economic Freedom index to measure economic freedom across countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3. See Easton and Walker (1997), Ayal and Karras (1998), Dawson (1998Dawson ( , 2003, De Haan and Sierman (1998), Gwartney, Lawson, and Holcombe (1999), Wu and Davis (1999), De Haan and Sturm (2000), Carlsson and Lundstrom (2002), Justesen (2008), Xu and Li (2008), Faria andMontesinos (2009), andGwartney (2009). relationship between the level of economic freedom and income inequality, Scully (2002) finds that higher levels of economic freedom are associated with lower levels of income inequality. Both studies use the Fraser Institute Economic Freedom index to measure economic freedom across countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xu and Li (2008) collected data for a sample of 104 countries between 1970 and 2003. They found that political freedom has positive effects on economic growth at later stages of social and economic development.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Scully [39] estimated that economic freedom promotes economic growth and positive association. Xu and Li [40] examined economic freedom has strong support and greater positive effects on income convergence in the OECD countries. Ashby and Sobel [41] estimated that economic freedom has positively associated with higher income and a higher rate of income growth.…”
Section: Economic Freedom and Per Capita Incomementioning
confidence: 99%